Extraordinary creep resistance in a non-equiatomic high-entropy alloy from the optimum solid-solution strengthening and stress-assisted precipitation process. (1st January 2023) - Chen, Shuying; Qiao, Jingbo; Diao, Haoyan; Yang, Tengfei; Poplawsky, Jonathan; Li, Weidong; Meng, Fanchao; Tong, Yang; Jiang, Liang; Liaw, Peter K.; Gao, Yanfei
Highlights: A novel high entropy alloy (HEA), Al0.3 CoCrFeNi, is found to exhibit minimum creep strain rates that are several orders of magnitude lower than typical HEAs. Atom probe tomography and other advanced characterization tools reveal the formation of coherent L12 precipitates in early stage of creep deformation, followed by B2 precipitates in later stages. The enhanced creep resistance is quantitatively evaluated by various dislocation strengthening mechanisms. Abstract: Improving creep resistance has commonly been achieved by the optimization of alloy design that results into strong solid-solution strengthening and/or coherent precipitates for dislocation blockage. High-entropy alloys (HEAs), despite their single-phase solid-solution nature, only exhibit creep properties that are comparable to precipitate-strengthened ferritic alloys. Moreover, many HEAs are found to be plagued with many incoherent second phases after long-term annealing, which reduces the lifetime and thus prohibits their usage at elevated temperatures. The present work demonstrates the extraordinary creep resistance of a non-equiatomic Al0.3 CoCrFeNi HEA, in which the creep strain rate is found to be several orders of magnitude lower than the Cantor alloy and its subsets. Using a suite of characterization tools such as atom probe tomography (APT) and transmission electron microscopy (TEM), it was shown that a B2 precipitate phase that has been widely seen during annealing is suppressed during the early stage of the creep deformation. Currently, metastable and coherent L12 precipitates emerge and provide significant creep strengthening. This observation is rationalized by the coupling between the applied stress and the lattice mismatch. In the range of 973 ∼ 1033 K, the stress exponent and activation energy were determined to be 3–6.53 and 390–548.2 kJ·mol −1, respectively. The creep lifetime, on the other hand, is comparable to Cantor subset alloys because the precipitate free zone near the grain boundaries does not provide sufficient constraint for the grain boundary cavity growth. The present work provides a pathway to design novel HEAs with improved creep resistance. Graphical abstract: Image, graphical abstract